Mineralogical Variations within Two Widespread Holocene Tephra Layers from Cascade Range Volcanoes, U.S.A. - Juvigné, Étienne; Porter, Stephen (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1985)
ABSTRACTThe heavy mineral content of volcanic ash from Mount Mazama (layer O) and Mount St. Helens (layer Yn) decreases downwind from each volcano. The transparent heavy mineral suite of layer O also varies downwind because of differences in specific gravity and shape of the grains, reflecting sorting processes during transportation in the atmosphere. In the first few tens of kilometers from the volcano some values strongly deviate from the general trend. This is attributed to exceptional turbulence at the time of eruptions in the vicinity of the vent.